RCAs within Western Europe - Jens Oelgemöller; Andreas Westermeier (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2009)
This paper analyses the revealed comparative advantage for six European countries: Austria, France, Germany, Italy, the Netherlands and the UK. The results can be summarized as the follows: Italy always had a trade specialisation index which was well above average. Apart from Italy, whose trade performance index decreased substantially, changes in the trade performance index were fairly small. Austria, Germany and the Netherlands faced increasing average RCA-values (but they remain positive), while France, Italy and the United Kingdom faced decreasing average RCA-values. Italy's RCA-value correlated negatively with the other countries (except for the correlation between Italy and France), while the other countries (Austria, France, Germany, the Netherlands and the United Kingdom) faced a positive correlation with each other. The top ten sectors with the highest RCA-value, shared about 50 % of total exports in France, Germany and the Netherlands. In the other three countries, the share was less than 40%. Regarding the top five sectors, specialization can be found only in Germany (>40 %) and the Netherlands (>30 %) whereas in the other countries the share was less than 20%. Germany and the Netherlands were the countries, in which most of the top 10 export sectors in 2005 also had CCA. The other countries had several top 10 export sectors with RCA-indicators significantly below the CCA-benchmarks.
Keywords: F14; 330; Revealed Comparative Advantage; Comparative Cost Advantage; Trade; Komparativer Kostenvorteil; Internationale Arbeitsteilung; Österreich; Frankreich; Deutschland; Italien; Niederlande; Großbritannien